Pilot‐based detection for DVB‐T passive coherent location radars. Issue 6 (14th April 2020) - Mahfoudia, Osama; Horlin, François; Neyt, Xavier
Abstract : This study investigates the feasibility of pilot‐based detection for passive coherent location (PCL) radars exploiting digital video broadcasting‐terrestrial (DVB‐T) signals. The DVB‐T signal is formed by two parts: a data signal and a pilot signal. The parameters of the pilot signal are known thanks to the DVB‐T standards that permit the generation (at the receiver) of the pilot signal. The pilot recovery technique, based on the known DVB‐T standard, is utilised in DVB‐T based PCL systems to reduce the number of the reception channels by considering a locally generated pilot signal as a reference signal. Consequently, no reference channel is required, which reduces the cost and the complexity of the resulting PCL system. In this work, the authors propose a signal processing method to achieve this goal. They consider theoretical analysis, simulations and real‐data results to validate the feasibility of such a system.